Isothermal dust models of Herschel-ATLAS star galaxies - Smith, D; Hardcastle, M; Jarvis, M; Maddox, S; Dunne, L; Bonfield, D; Eales, S; Serjeant, S; Thompson, M; Baes, M; Clements, D; Cooray, A; et al. (2013)
We use galaxies from the Herschel-ATLAS (H-ATLAS) survey, and a suite of ancillary simulations based on an isothermal dust model, to study our ability to determine the effective dust temperature, luminosity and emissivity index of 250 μm selected galaxies in the local Universe (z < 0.5). As well as simple far-infrared spectral energy distribution (SED) fitting of individual galaxies based on X2 minimization, we attempt to derive the best global isothermal properties of 13 826 galaxies with reliable optical counterparts and spectroscopic redshifts. Using our simulations, we highlight the fact that applying traditional SED fitting techniques to noisy observational data in the Herschel Space Observatory bands introduces artificial anticorrelation between derived values of dust temperature and emissivity index. This is true even for galaxies with the most robust statistical detections in our sample, making the results of such fitting difficult to interpret.We apply a method to determine the best-fitting global values of isothermal effective temperature and emissivity index for z < 0.5 galaxies in H-ATLAS, deriving Teff = 22.3 ± 0.1K and β = 1.98 ± 0.02 (or Teff = 23.5 ± 0.1K and β = 1.82 ± 0.02 if we attempt to correct for bias by assuming that Teff and βeff are independent and normally distributed). We use our technique to test for an evolving emissivity index, finding only weak evidence. The median dust luminosity of our sample is log10(Ldust/L⊙) = 10.72 ± 0.05, which (unlike Teff) shows little dependence on the choice of β used in our analysis, including whether it is variable or fixed. In addition, we use a further suite of simulations based on a fixed emissivity index isothermal model to emphasize the importance of the H-ATLAS PACS data for deriving dust temperatures at these redshifts, even though they are considerably less sensitive than the SPIRE data. Finally, we show that the majority of galaxies detected by H-ATLAS are normal star-forming galaxies, though with a substantial minority (~31 per cent) falling in the Luminous Infrared Galaxy category. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.